Risk Factors for Carotid Restenosis in Patients After Eversion Endarterectomy vs Stenting: A Single-Center Experience. (April 2023) - Petrovic, Jovan; Ilijevski, Nenad; Sagic, Dragan; Antonic, Zelimir; Tanaskovic, Slobodan
The primary aim of the presented study is to analyze and compare the rate of carotid restenosis in patients after eversion carotid endarterectomy (eCEA), primary carotid angioplasty and stenting (CASp), and stenting for carotid artery restenosis after previous eCEA (CASr). The secondary aim is to compare clinical outcomes in patients with carotid restenosis. The total number of patients with evident carotid restenosis was 223 (24.8%). In patients with eCEA, significant carotid restenosis rate was 12.7%, in the CASp group 18.7%, and CASr 6.7%. Patients with carotid restenosis were asymptomatic in 95.1% of cases. Patients in the CASp group experienced transient ischemic attack more than patients with eCEA ( P = .007), while no difference was observed regarding cerebrovascular insult (CVI). The incidence of carotid restenosis was higher in CASp patients, and increased during the follow-up. The majority of patients are asymptomatic post-procedural and the degree of carotid restenosis does not correlate with the occurrence of postoperative symptoms. High low-density lipoprotein cholesterol (LDL-C) levels, low high-density lipoprotein cholesterol (HDL-C) levels, smoking, and a history of vascular surgery correlate with higher degrees of carotid restenosis. The most important factor in the prevention of carotid restenosis is risk factor control as well as adequate pharmacological therapy.